A Novel External Auditory Canal Squamous Cell Carcinoma Cell Line Sensitive to CDK4/6 Inhibition. (5th February 2023) - García‐Marín, Rocío; Cabal, Virginia N.; Fernández‐Cedrón Bermejo, Carmen; Riobello, Cristina; Suárez‐Fernández, Laura; Codina‐Martínez, Helena; Navarro‐García, Ainhoa; Lorenzo‐Guerra, Sara Lucila; García‐Martínez, Jorge; Vivanco, Blanca; López, Fernando; Llorente, José Luis; et al.
Abstract: Objective: To characterize cell line CAE606 derived from a squamous cell carcinoma (SCC) of the external auditory canal (EAC) and to show its usefulness as a model for testing candidate therapeutic agents. Study Design: Preclinical translational research. Setting: Biomedical research institute. Methods: The cell line was initiated from a moderately differentiated T2N0M0 EAC SCC. We studied its histologic and genetic features as well as growth and invasion parameters. Sensitivity to cell CDK4/6 cell cycle inhibitor palbociclib was analyzed. Results: CAE606 cells expressed heavy molecular weight cytokeratin, p63, and vimentin. The population doubling time was 25.8 hours, and the cells showed fast collective cell migration in a wound‐healing assay. Short tandem repeat analysis confirmed it to be derived from the primary tumor of the patient. Next‐generation sequencing revealed alterations in cell cycle regulation genes, including inactivating mutations in CDKN2A and TP53 and high‐level amplification of CCND1 and EGFR . CAE606 showed a strong decrease of phospo‐Rb expression upon exposure to the CDK4/6 inhibitor palbociclib, causing significant growth inhibition with an IC50 of 0.46 µM. Conclusion: This is the first report of a stable EAC SCC cell line. Its genetic features make it a useful tool for preclinical testing of new therapeutic agents for EAC SCC, particularly those targeting cell cycle regulation in combination with radio‐ and chemotherapy or other specific signaling pathway inhibitors.